Effect of creep-feeding supplementation on growth, and metabolic and reproductive characteristics of Nellore heifers - Paixão, Robert Teixeira da (2021)
Objectives were to evaluate the effects of supplementation at pre-weaning phase on growth performance, metabolic, and reproductive characteristics of Nellore heifers. Forty-two Nellore female calves (average age = 100 ± 25 d; average initial body weight [BW] = 113.4 ± 16.6 kg) were randomly assigned to one of two treatments (n = 21) at the pre-weaning phase: control = heifers received mineral mix supplementation; and supplemented = heifers received 6 g/kg BW of a concentrate supplement. During the post-weaning phase, all heifers received 6 g/kg BW of a concentrate supplement. The experiment lasted 320 d. Supplemented heifers had greater average daily gain (ADG) than control heifers at pre-weaning phase and, consequently, were heavier at weaning and final of growing phase (P < 0.05). However, pre-weaning supplementation did not influence (P > 0.05) the body measurements or body weight at the end of growing period. Greater (P < 0.05) rib fat was observed in supplemented heifers. Concentrations of metabolites and the and conception rates were not affected (P > 0.05) by pre- weaning supplementation. Thus, supplementing heifers at the pre-weaning phase improved growth performance at weaning and body adiposity however, without additional performance or metabolic characteristics. Keywords: Beef cattle. Bos indicus. Growth. Heifer. Puberty.